Investigating Efl Teachers’ Beliefs in the Use of Information Communication Technologies for Self-Initiated Professional Development - Mitiku Garedew Tessema; Girma Gezahegn Belihu (JALL (Journal of Applied Linguistics and Literacy), 2023)
Although teachers in Ethiopia are given pre-service training to upgrade their pedagogical knowledge and teaching proficiency, they may not be fully prepared for all the challenges they will face throughout their careers. This is particularly true in the current situation that requires teachers to be able to meet the changing needs of the current learners that use technology. The federal ministry of education has been making efforts to provide teachers at all levels concerning information communication technologies (ICTs) utilization in their educational activities.  In addition to the government–initiated training packages, teachers are expected to familiarize themselves with ICTs through their own self-initiated efforts. The purpose of this study was to investigate the use of ICTs in University EFL teachers’ Self-initiated professional development. The study participants were 35 EFL university teachers from Addis Ababa Science and Technology University. They were selected using total population sampling. Concurrent mixed methods were employed in the study. The data were collected using a questionnaire and semi-structured interviews. The data were then analyzed separately and finally mixed during the discussion of the data. The findings of the study indicated that teachers' beliefs about the use of ICTs in self-initiated professional development were positive.